What drives customer satisfaction and word of mouth in mobile commerce services? A UTAUT2-based analytical approach. Issue 1 (28th October 2019) - Kalinić, Zoran; Marinković, Veljko; Djordjevic, Aleksandar; Liebana-Cabanillas, Francisco
Abstract : Purpose: The purpose of this paper, which is based on the UTAUT2 model, is to develop and evaluate a predictive model of customer satisfaction related to mobile commerce (m-commerce) and the willingness to recommend this service to others. Design/methodology/approach: The study was conducted based on a sample of 402 respondents. Confirmative factor analysis was used to evaluate the validity of the model, while structural equation modeling (SEM) was used to test the hypotheses. Finally, artificial neural networks were used to rank the influence of the significant predictors obtained by SEM. Findings: Trust was found to be the most significant driver of customer satisfaction, followed by performance expectancy and perceived value. In addition, affective commitment and satisfaction were identified as the strongest predictors of word of mouth (WOM). Originality/value: The originality/value of the paper lies in the establishment of the connection between the independent variables of the UTAUT 2 model – trust, satisfaction, affective and continence commitment and WOM. Additionally, it is one of a small number of studies investigating customer commitments and their influence on WOM in m-commerce.